The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1523/jneurosci.0857-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Selective Loss of Catecholaminergic Wake–Active Neurons in a Murine Sleep Apnea Model

Abstract: The presence of refractory wake impairments in many individuals with severe sleep apnea led us to hypothesize that the hypoxia/ reoxygenation events in sleep apnea permanently damage wake-active neurons. We now confirm that long-term exposure to hypoxia/ reoxygenation in adult mice results in irreversible wake impairments. Functionality and injury were next assessed in major wake-active neural groups. Hypoxia/reoxygenation exposure for 8 weeks resulted in vacuolization in the perikarya and dendrites and marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(126 citation statements)
references
References 68 publications
(81 reference statements)
5
118
0
3
Order By: Relevance
“…We found that NE cell counts in these cell groups were similar to those in untreated rats (16,19) and did not differ between CIH-and sham-exposed rats of the present study. This is consistent with qualitative observations in mice suggesting that only the locus coeruleus, but not other brainstem NE cell groups, is susceptible to CIH-induced damage (39). The absence of changes in relevant cell numbers in our CIH rats further supports our interpretation that CIH elicited sprouting of NE terminals.…”
Section: Increased Ne and 5-ht Terminal Density In The XII Nucleus Afsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that NE cell counts in these cell groups were similar to those in untreated rats (16,19) and did not differ between CIH-and sham-exposed rats of the present study. This is consistent with qualitative observations in mice suggesting that only the locus coeruleus, but not other brainstem NE cell groups, is susceptible to CIH-induced damage (39). The absence of changes in relevant cell numbers in our CIH rats further supports our interpretation that CIH elicited sprouting of NE terminals.…”
Section: Increased Ne and 5-ht Terminal Density In The XII Nucleus Afsupporting
confidence: 92%
“…It has been reported that, in mice, prolonged exposure to CIH elicits cellular changes characteristic of neuronal damage in NE neurons of the locus coeruleus (39). If this effect also occurred in our CIH-exposed rats and involved those brainstem NE neurons that have axonal projections to the XII nucleus, a decrease, rather than an increase, of NE terminals would be expected.…”
Section: Increased Ne and 5-ht Terminal Density In The XII Nucleus Afmentioning
confidence: 50%
“…Long-term intermittent hypoxia (LTIH) across the sleep-predominant period of a circadian period is an established model of sleep apnea oxygenation (Gozal et al, 2001;Decker et al, 2003;Veasey et al, 2004a,b;Kheirandish et al, 2005;Zhan et al, 2005;Polotsky et al, 2006). An automated nitrogen/oxygen gas delivery system (Oxycycler model A84XOV; Biospherix, Redfield, NY) was used to deliver hypoxia/reoxygenation, using our previously described protocol (Veasey et al, 2004a,b;Zhu et al, 2007). Briefly, this system produces reductions in ambient oxygen level from 21 to 10% for 5 s every 90 s for LTIH and from 21 to 20% for 5 s every 90 s for sham LTIH, resulting in fluctuations in oxyhemoglobin saturation from 94 -98% to 76 -84% in LTIH and 96 -98 to 96 -97% in sham LTIH (Veasey et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Exposure to hypoxia/reoxygenation events in rodents, modeling oxygenation patterns in severe sleep apnea, results in neural injury in select groups of neurons including pyramidal, Purkinje, catecholaminergic wake neurons, and upper airway dilator motoneurons (Gozal et al, 2001;Decker et al, 2003Decker et al, , 2005Veasey et al, 2004a;Kheirandish et al, 2005;Zhan et al, 2005a,b;Zhu et al, 2007). Long-term exposure to hypoxia/reoxygenation impairs hypoglossal whole-nerve responsiveness to both glutamatergic and serotonergic excitation of hypoglossal motoneurons (Veasey et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…(21) Além disso, foi observado que a hipóxia crônica recorrente induz a lesão irreversível e funcionalmente significativa em grupos neuronais ativos na vigília. (22) A morbidade neurocognitiva na apneia do sono obstrutiva tem sido estudada em roedores submetidos a hipóxia intermitente e/ou a alteração do padrão de sono. Foi demonstrado que os eventos hipóxicos recorrentes prejudicam a memória de trabalho espacial e o aprendizado.…”
Section: Estudos Em Animaisunclassified